Reflexões sobre loucura e racismo a partir da literatura de Lima Barreto - Carvalho, Paulo Dourian Pereira de (2024)
This research aimed to reflect on racism and madness found in the literature of the black writer Lima Barreto (1881-1922). Through content analysis and an interdisciplinary perspective that involves dialogue between literature, sociology, anthropology, political science, and history, it was sought to produce an essay to feed into the discussions, bringing other approaches that could broaden the debate about Barreto's work, which is taken here as a testimony of a black man who did not survive the oppression of race and class. It is seen that madness and racism, as well as poverty, sadness, loneliness, and resentment, crossed the writer's life. From an intersectional perspective that considers the crossing of social markers of difference such as race, class and madness, it is understood that the writer was a victim of the racism that was structured in post-slavery Brazilian society. In that context, the lack of opportunities was exacerbating, the absence of policies to integrate "freed" black people, the traumas stemming from the enslavement regime, the denial of the culture of the enslaved, the unspeakable and unnameable pain of those who had also reached "the bottom", to paraphrase the Italian philosopher Giorgio Agamben, when referring to the "Muslims", that is, the dehumanized, of the Auschwitz concentration camps. For this study, some of the works that will help us immerse ourselves in the immensity of Barreto's thoughts are: Recordações do escrivão Isaías Caminha, The Sad End of Policarpo Quaresma, Diário íntimo, Clara dos Anjos, his short stories, as well as the biographies written by Francisco Assis Barbosa and Lilia Moritz Schwarcz. In interpreting the analyzed content, authors such as Giorgio Agamben, Frantz Fanon, Grada Kilomba, Michel Foucault, Achille Mbembe, Djamila Ribeiro, Silvio Almeida and others will be used to help echo Lima Barreto's voice. He is considered to have been a witness and a resistance at a time when black people, the insane, and the poor were imprisoned by a hygienist policy influenced by eugenics. Surviving in precariousness, with a shortage of resources, a family crisis, and alcoholism until he plunged into delirium and mental suffering, without gaining recognition or space on the intellectual scene, Lima Barreto resisted to the point of not allowing his black presence to be drowned out by the whitening steamroller. In the face of the madness, which is a racist society, the writer left us his testimony: an extensive and rich black literature, critical of racism and the cruelty of life in an asylum.